An Exploratory Study Using Cortisol to Describe the Response of Incarcerated Women IPV Survivors to MAMBRA Intervention - Janette Y. Taylor; Ezra C. Holston (Nursing Research and Practice)
Objective. To determine if incarcerated women survivors of IPV had a physiological response to the Music and Account-Making for Behavioral-Related Adaptation (MAMBRA) intervention, as measured by cortisol levels. Methods. A single-group repeated measures designed exploratory study was used to pilot-test MAMBRA. A convenience sample (n=33) was recruited in a Midwestern women’s correctional facility. Serving as their own control, participants provided demographics and pre-/post-MAMBRA salivary samples while attending four MAMBRA sessions. Baseline data were compared to participants’ data collected over the remaining 3 MAMBRA sessions. Data were analyzed with descriptive and univariate statistics with an alpha of .05 and post-hoc power of .65. Results. Participants were predominantly White (52%), single (80%), and early middle-aged (x-AGE=38.7±9.4), with a history of physical/nonphysical spousal abuse. Using a subsample (n=26), salivary cortisol decreased between the pre-/post-MAMBRA over the sessions (F(3,75)=4.59, p<.01). Conclusion. Participants had a physiological response to the MAMBRA intervention as evidenced by the decreased cortisol between the pre-/post-MAMBRA. This is the first step in examining MAMBRA’s clinical utility as an intervention for female IPV survivors. Future longitudinal studies will examine MAMBRA’s effectiveness given this change in cortisol.